Current Research Trends in the Application of In Vitro Three-Dimensional Models of Liver Cells - Chawon Yun; Sou Hyun Kim; Young-Suk Jung (Pharmaceutics, 2022)
The liver produces and stores various nutrients that are necessary for the body and serves as a chemical plant, metabolizing carbohydrates, fats, hormones, vitamins, and minerals. It is also a vital organ for detoxifying drugs and exogenous harmful substances. Culturing liver cells in vitro under three-dimensional (3D) conditions is considered a primary mechanism for liver tissue engineering. The 3D cell culture system is designed to allow cells to interact in an artificially created environment and has the advantage of mimicking the physiological characteristics of cells in vivo. This system facilitates contact between the cells and the extracellular matrix. Several technically different approaches have been proposed, including bioreactors, chips, and plate-based systems in fluid or static media composed of chemically diverse materials. Compared to conventional two-dimensional monolayer culture in vitro models, the ability to predict the function of the tissues, including the drug metabolism and chemical toxicity, has been enhanced by developing three-dimensional liver culture models. This review discussed the methodology of 3D cell cultures and summarized the advantages of an in vitro liver platform using 3D culture technology.